Electrical Performance of a Molecular Organic Semiconductor under Thermal Stress. Issue 11 (27th January 2017) - Seifrid, Martin; Ford, Michael J.; Li, Mingqi; Koh, Kyoung Moo; Trefonas, Peter; Bazan, Guillermo C.
Abstract : The high temperature performance of organic field‐effect transistors based on a molecular organic semiconductor with intermediate dimensions, namely X2, is evaluated. Hole mobility is stable, even at 200–250 °C. Changes in device characteristics at high temperature are reversible across multiple cycles of high temperature operation. Measurements at high temperature exhibit larger hysteresis, while at low temperature one observes the emergence of ambipolar transport.